NleB/SseK-catalyzed arginine-glycosylation and enteropathogen virulence are finely tuned by a single variable position contiguous to the catalytic machinery. Issue 36 (19th August 2021) - García-García, Ana; Hicks, Thomas; El Qaidi, Samir; Zhu, Congrui; Hardwidge, Philip R.; Angulo, Jesús; Hurtado-Guerrero, Ramon
Abstract : The NleB and SseK glycosyltransferases glycosylate arginine residues of mammalian proteins with different substrate specificities. We uncover that these differences rely on a particular second-shell residue contiguous to the catalytic machinery. Abstract : NleB/SseK effectors are arginine-GlcNAc-transferases expressed by enteric bacterial pathogens that modify host cell proteins to disrupt signaling pathways. While the conserved Citrobacter rodentium NleB and E. coli NleB1 proteins display a broad selectivity towards host proteins, Salmonella enterica SseK1, SseK2, and SseK3 have a narrowed protein substrate selectivity. Here, by combining computational and biophysical experiments, we demonstrate that the broad protein substrate selectivity of NleB relies on Tyr284 NleB/NleB1, a second-shell residue contiguous to the catalytic machinery. Tyr284 NleB/NleB1 is important in coupling protein substrate binding to catalysis. This is exemplified by S286Y SseK1 and N302Y SseK2 mutants, which become active towards FADD and DR3 death domains, respectively, and whose kinetic properties match those of enterohemorrhagic E. coli NleB1. The integration of these mutants into S. enterica increases S. enterica survival in macrophages, suggesting that better enzymatic kinetic parameters lead to enhanced virulence. Our findings provide insights into how these enzymes finely tune arginine-glycosylation and, in turn, bacterial virulence. In addition, our data show how promiscuous glycosyltransferases preferentially glycosylate specific protein substrates.